Implementation of administrative reforms within the framework of Uzbekistan’s "Electronic Government" policy - А. Otajonov Elyorbek (DEVELOPMENT OF EDUCATION AND SCIENCE IN THE ERA OF DIGITAL TRANSFORMATION, 2025)
The article analyzes the content and essence of the administrative reforms being carried out under the “E-Government” policy in the context of the New Uzbekistan. Within the framework of the 2017-2021 Action Strategy, the process of modernizing public administration began, and the introduction of the "e-government" concept plays a crucial role in providing citizens with quality and prompt services, ensuring openness and transparency, and reducing bureaucratic barriers. The article discusses the use of digital technologies to enhance governance efficiency and strengthen public trust, illustrated by examples such as the Electronic State Services Portal (my.gov.uz), the Open Data Platform (data.egov.uz), and the Public Discussion Portal for Normative Legal Acts (regulation.gov.uz). Additionally, it emphasizes the achievements of these reforms, including the reduction of corruption risks, the expansion of citizen participation in decision-making, and the increased accountability of government agencies.